Mystical Discourse on the Last Days: A Historical and Comparative Analysis of Shia Islamic Thought - Reisi, Ehsan; Rezaei, Ebrahim; Jafari, Elham (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
The scholarship on the last days (ākhir al-zamān) has predominantly centered around religious and historical texts, leaving out the rich mystical sources within Shia culture. This study aims to fill this gap by investigating Islamic mysticism from the second to the tenth century AH, written in Persian and Arabic. By delving into these mystical writings, this research intends to shed light on the transformative impact of discussions in the last days and the way mystics approached this subject. The overlooked evolution of these writings remains significant for grasping the continued relevance of discussions on the last days in contemporary Shia society and other religions. The research suggests that discussions surrounding the concept of the last days have been a source of considerable debate among mystics dating back to the first mystical tradition, with these interpretations often incorporating elements from several religions, becoming more intricate in subsequent periods, and influencing Shia culture today.